Perennials for the pacific northwest ebook 500 best plants for flower gardens. - Wingate, Marty (2013)
This is the A-List of flowering plants recommended for Pacific Northwest gardens—updated to include the current crop of available perennials—in a lavishly photographed and definitive guide, which will aide in selecting the best perennials to build a successful garden. These are the plants that can winter over and return with showy brilliance the following year, and in the gentle climate of the northwest, there are so many to choose from. But which is the best white flower to plant next to a pink rhodie in a partial-shade setting? And can a garden have pretty perennials without a lot of watering? Figuring out what works well together is such a puzzle! Perennials for the Pacific Northwest explains all of that, plus how best to take care of your plants. It features full descriptions of 500 plants, each of the fully described plants includes a color photograph; selected plants from the lists are pictured.